Investigations of Acacia modesta Wall. leaves for in vitro anti-diabetic, proliferative and cytotoxic effects - Bushra Saleem; Muhammad Islam; Hamid Saeed; Fariha Imtiaz; Maryam Asghar; Zikria Saleem; Azra Mehmood; Surriya Naheed (Universidade de São Paulo, 2018)
ABSTRACT The leaves of Acacia modesta Wall. have been shown to possess diverse pharmacological properties. Therefore, we aimed at evaluating anti-diabetic, cytotoxic and proliferative effects of extracts of Acacia modesta Wall. leaves. After evaluating the primary and secondary metabolites, anti-diabetic activity of various extracts was assessed by α-amylase inhibition, glucose uptake by yeast cells and non-enzymatic glycosylation of hemoglobin assay. Cytotoxicity and proliferative potential was assessed by MTT (3-(4,5-dimethylthiazol-2-yl)-2,5-diphenyltetrazolium bromide) and short term proliferation assays, respectively, using human liver carcinoma cell line, HepG2. Among other extracts, chloroform extract exhibited 34.16% inhibition of α-amylase, 90.65% inhibition of hemoglobin glycosylation and 94.75% glucose uptake employing α-amylase inhibition, non-enzymatic glycosylation of hemoglobin and glucose uptake by yeast cells assays, respectively. Moreover, extracts exhibited no significant effects on HepG2 cell viability and proliferation. So, this data suggested that chloroform extract of leaves of Acacia modesta Wall., exhibited higher anti-hyperglycemic activity in comparison to extracts in other solvents, while no extract demonstrated cytotoxic and proliferation effects when tested using HepG2 cell line.